Characterization of silicon nanowire transistor - Hani Taha Al Ariqi; Waheb A. Jabbar; Yasir Hashim; Hadi Bin Manap (Universitas Ahmad Dahlan, 2019)
This paper analyses the temperature sensitivity of Silicon Nanowire Transistor (SiNWT) depends on the diameter (D.ch) of channel. In addition, it also investigates the possibility of utilizing SiNWT as a Nano- temperature sensor. The MuGFET simulation tool has been utilized to conduct a comprehensive simulation to evaluate both electrical and temperature characteristics of SiNWT. Current-voltage characteristics with different values of temperature and with a varying diameter of the Nano wire channel (D.ch = 80, 40, 20 and 10 nm), were simulated. Diode operating mode connection of the transistor is suggested for measuring the temperature sensitivity of SiNWT. As simulation results demonstrated, the best temperature sensitivity was occurred at lower temperature with increasing the channel diameter. We also illustrate the impact of varying temperature and channel diameter on electrical characteristics of SiNWT including, Subthreshold Swing (SS), Threshold voltage (V.th), and Drain-induced barrier lowering (DIBL), which were proportionally increased with the operating temperature.